Ethnomathematics Exploration At The State Museum Of North Sumatra - Sagala, Siti Aisyah; Hasanah, Rusi Ulfa (Universitas Wiralodra, 2023)
Ethnomatematics can be used as a way to convey local culture and mathematics simultaneously, because ethnomatematics is a combination of culture and mathematics. The State Museum of North Sumatra is one of the historic buildings of North Sumatra which contains ethnomathematics concepts. This study aims to explore the ethnomathematics contained in the State Museum of North Sumatra. This research is a qualitative descriptive study with an ethnographic approach. The research subject was one of the officers of the State Museum of North Sumatra. Data collection techniques include observation, interviews, documentation and literature studies. The results of the study prove that there are geometric shapes and geometric shapes in the North Sumatra State Museum building and several historical heritage objects in the North Sumatra State Museum. And there is the concept of geometric transformation in the ornaments of the North Sumatra State Museum.